2022
DOI: 10.7759/cureus.24685
|View full text |Cite
|
Sign up to set email alerts
|

Graded Epidural Anesthesia for Non-cardiac Surgery in the Prone Position in a Patient With Low Ejection Fraction

Abstract: Ischemic heart disease (IHD), also known as coronary artery disease, occurs due to the blockage of coronary arteries which reduces the blood supply of the myocardium. The main goal of the anesthetic management of IHD patients undergoing non-cardiac surgery is to maintain the balance between myocardial oxygen supply and demand. Here, we report the anesthetic management of an IHD patient with a low ejection fraction who was posted for percutaneous nephrolithotomy in the prone position. We opted for graded epidur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Mehdi Sanatkar et al also showed hemodynamic stability and no ST-T changes with low dose of bupivacaine and sufentanil in patients with CAD [11]. Jain M et al reported use a low dose of a local anaesthetic and an opioid during a graded epidural anaesthesia in patients w ith IHD and low ejection fraction posted for nephrolithotomy and observed a stable hemodynamic profile with adequate postoperative analgesia [12]. Due to the large network of venous plexus in the prostate gland's ability to absorb fluid, TURBT is often an hour-long treatment with an additional risk of fluid overload and TURP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Mehdi Sanatkar et al also showed hemodynamic stability and no ST-T changes with low dose of bupivacaine and sufentanil in patients with CAD [11]. Jain M et al reported use a low dose of a local anaesthetic and an opioid during a graded epidural anaesthesia in patients w ith IHD and low ejection fraction posted for nephrolithotomy and observed a stable hemodynamic profile with adequate postoperative analgesia [12]. Due to the large network of venous plexus in the prostate gland's ability to absorb fluid, TURBT is often an hour-long treatment with an additional risk of fluid overload and TURP syndrome.…”
Section: Discussionmentioning
confidence: 99%